Soto Sufi dari Madura dan Sate Rohani dari Madura by Zawawi Imron: A Structuralism Study - Wedawati, Mamik Tri (Journal of Education for Sustainability and Diversity, 2025)
Stories from Madura written by Zawawi Imron are known as the story that contains philosophical values. The stories could be said to be works full of wisdom and close to Madurese culture, especially those from Madura Island. Soto Sufi dari Madura dan Sate Rohani dari Madura are written with the background of the daily life of Madurese people. The intrinsic elements of the story, such as plot, setting, character and characterization, and theme, will be the story's strengths. The other vulnerable ideas are kept on the surface, and the story's deep structure already becomes a myth about Madurese culture. Stories that already transferred from one to another over the years will have a significant opportunity to deliver value from their stories, too. Applying the qualitative method, the research with the theory of structuralism by Levi-Strauss will answer the question about the structure of the story and the way of thinking of Madurese people. Some stories from 2 novels will drive the research into the people's hopes, expectations, and dreams at Madura, East Java. In their simple lives, society must work hard and strive hard to reach what they want and dream while they still maintain their culture where they feel very proud to be Madurese.